Correlation between Antimicrobial Resistance and Antimicrobial Consumption in Krabi Hospital - Wechakul, Mutchima; Rimdusit, Somruedee (Health Science Journal of Thailand, 2021)
Antimicrobial resistance become a current threat worldwide. The objective of this cross-sectional study was to examine the trend of antimicrobial resistance, and correlation of antimicrobial consumption and antimicrobial resistance in Krabi Hospital. The results of antimicrobial susceptibility and antimicrobial consumption were measured by daily defined dose during 2013-2019. The proportion of bacterial isolates-resist to antimicrobials and correlation of antimicrobial consumption were analyzed. The results showed that Pseudomonas aeruginosa retaining sensitivity to Amikacin with a statistically significant increased, the percent of resistant isolates was decreased (p-value = 0.042). Escherichia coli resistant to Piperacillin and Ertapennem decreased less than 10 folds, resistant to isolates to Piperacillin from 0.66% to 8.57% (p-value = 0.004), reistant to Ertapenem increased from 0.19% to 7.38% (p-value = 0.030). An antimicrobial consumption of Amikacin, Cefotaxime and Norfloxacin was statistically decreasesd (p-value = 0.027, 0.006, and 0.037). An increasing trends of using Ceftazidime, Piperacilin/Tazobactam, and Ertapenem was showed (p-value = 0.018, 0.006 and 0.030). Escherichia coli showed a positive correlation between drug consumption and resistant to Meropenem and Piperacilin/Tazobactam (r = 0.96, p-value <0.001, and r = 0.79, p-value =0.036).